Casino Knokke. - Casino, Knokke; Galerie Jan De Maere, Brussel (Brussel : Galerie Jan De Maere, 1981)
Taulé, Antonio ; de Stefani, Massimo ; Milcovitch, Mircea ; Lambrecht, Constant ; Moskovtcheno, Michel ; Houwen, Joris ; Cortier, Amédée ; Verhé, Arnold ; Senez, Alain ; Van den Heede, Raeoul ; etc.
Casino Knokke, Galerie Jan De Maere, Brussel, 4-22 april '81
boek